Free trade agreements and the SADC economies - Lewis, Jeffrey D.; Robinson, Sherman; Thierfelder, Karen (International Food Policy Research Institute, 2001)
Countries in Southern Africa have engaged in a variety of trade liberalization initiatives. In this paper, the authors use a multi-country, computable general equilibrium (CGE) model to analyze the impact of trade liberalization on countries, sectors, and factor. To focus on trade flows among countries in Southern Africa, the model includes seven countries in the region (South Africa, Botswana, Malawi, Mozambique, Tanzania, Zambia, and Zimbabwe), the rest of SADC, the rest of Sub-Saharan Africa, and five other aggregate regions (the EU, High-Income Asia, Low-Income Asia, North America, and the rest of the world). First, they analyze the FTA between South Africa and the EU. Then, they consider how the rest of Southern Africa might respond: (1) by enforcing a SADC FTA; (2) by exploiting advantages of unilateral access to the EU in addition to a SADC FTA; and (3) by entering an FTA with the EU and other SADC countries.